INVESTIGATION ON BIODIVERSITY AND CONSERVATION OF FRESHWATER FISHES IN INDONESIA - Sudarto Sudarto; Emmanuel Paradis (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2012)
Indonesia is one of the richest regions in the world in terms of biodiversity. However, recent evidence has shown that tropical forests destruction has maintained at a high rate over the last few years in this country. At the same time, living resources in Indonesian freshwater ecosystems are important: this country ranks at number seven in terms of production of inland capture fisheries with 323,150 tonnes in 2008. Freshwater fishes represent 42% of the total estimated ichthyofauna, concentrated in 0.01% of the total water covered environment. This environment is closer to human activities, making it critically vulnerable to adverse impacts. Furthermore, there has been some recent debates on the general sustainability of fisheries and aquaculture production systems. This research was focused on initiating a multi-scale study of fish biodiversity in freshwater environments. Two specific actions have been started. A review based on the analyses of the existing scientific literature and of databases on fish taxonomy and distributions. In parallel to this work, a global analysis of the distribution of fish diversity in Indonesia was undertaken. This work aims at identifying the major features of this resource as well as its current and future threats.